Exploring the factors in information seeking behavior: a perspective from multinational COPD online forums. (19th July 2021) - Boyce, LeAnn; Harun, Ahasan; Prybutok, Gayle; Prybutok, Victor R
Summary: This research establishes a theoretical framework for evaluating antecedents of the information seeking behaviors of online forum participants with chronic obstructive pulmonary disease (COPD). We evaluated the proposed framework using partial least squares structural equation modeling (PLS-SEM) after gathering data using a cross-sectional survey. We subsequently assessed the framework using importance−performance map analysis (IPMA). Findings suggest that perceived ease of use does not singularly influence COPD forum users' information seeking behavior. IPMA analysis reveals that the opportunity to interact with other forum members creates the greatest impact on COPD forum users' mindsets, among all the indicators. For healthcare professionals, the results of this study provide a blueprint in terms of utilizing COPD online forums to foster recurrent associations among forum administrators and users and by creating a strong social and informational resource for COPD information seekers.